Kingship and Prophecy in Thomas Mofolo’s Chaka - Lilford, Grant (Christianity & literature, 2012)
In his third and best-known novel, Chaka, Lesotho writer Thomas Mofolo makes no explicit references to Christianity, marking a departure from the intentionally evangelical character and language of his earlier works, Traveller to the East and Pitseng. I argue, however, that the novel alludes to the Bible, notably 1 and 2 Samuel, to make a powerful statement on the nature of kingship in traditional African society, especially in light of human sinfulness and frailty. Mofolo defends the righteousness of African ideals of society and kingship, even as he reveals how human frailty and ambition make those ideals unsustainable. Mofolo uses the Biblical narrative to illuminate his extensive awareness of Southern African history and culture, showing the specific relevance of the Christian Gospel to his society.